Hydrogen Bond Stability of Quinazoline Derivatives Compounds in Complex against EGFR using Molecular Dynamics Simulation - Herlina Rasyid; Bambang Purwono; Thomas S Hofer; Harno Dwi Pranowo (Indonesian Journal of Chemistry, 2019)
Lung cancer was a second common cancer case due to the high cigarette smoking activity both in men and women. One of protein receptor which plays an important role in the growth of the tumor is Epidermal Growth Factor Receptor (EGFR). EGFR protein is the most frequent protein mutation in cancer and promising target to inhibit the cancer growth. In this work, the stability of the hydrogen bond as the main interaction in the inhibition mechanism of cancer will be evaluated using molecular dynamics simulation. There were two compounds (A1 and A2) as new potential inhibitors that were complexed against the EGFR protein. The dynamic properties of each complexed were compared with respect to erlotinib against EGFR. The result revealed that both compounds had an interaction in the main catalytic area of protein receptor which is at methionine residue. Inhibitor A1 showed additional interactions during simulation time but the interactions tend to be weak. Inhibitor A2 displayed a more stable interaction. Following dynamics simulation, binding free energy calculation was performed by two scoring techniques MM/GB(PB)SA method and gave a good correlation with the stability of the complex. Furthermore, potential inhibitor A2 had a lower binding free energy as a direct consequence of the stability of hydrogen bond interaction.